2017
DOI: 10.1016/j.psychres.2017.02.059
|View full text |Cite
|
Sign up to set email alerts
|

Insight and suicidality in psychosis: A cross-sectional study

Abstract: Insight and suicidality in psychosis: A crosssectional study, Psychiatry Research, http://dx.doi.org/10.1016Research, http://dx.doi.org/10. /j.psychres.2017 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its final citable form. Please note that during the production pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
2
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 53 publications
4
15
2
3
Order By: Relevance
“…Also, previous suicide attempts, but not baseline insight scores, were associated with suicidal behaviours in the multivariable models, with 'significant' (at p<0.05) HRs ranging from 2.75 (AESOP) to 5.31 (GAP), hence a strong association. In other words, previous suicide attempts seem to explain in part the apparent association between insight and suicidal behaviour in psychosis, which is consistent with a previous cross-sectional study (Massons et al, 2017). Nevertheless, up to 42% of suicide completers with schizophrenia spectrum disorder have no previous suicide attempts (LopezMorinigo et al, 2014b;Lopez-Morinigo et al, 2016).…”
Section: Previous Suicide Attempts and Depression Were Related To Bassupporting
confidence: 80%
“…Also, previous suicide attempts, but not baseline insight scores, were associated with suicidal behaviours in the multivariable models, with 'significant' (at p<0.05) HRs ranging from 2.75 (AESOP) to 5.31 (GAP), hence a strong association. In other words, previous suicide attempts seem to explain in part the apparent association between insight and suicidal behaviour in psychosis, which is consistent with a previous cross-sectional study (Massons et al, 2017). Nevertheless, up to 42% of suicide completers with schizophrenia spectrum disorder have no previous suicide attempts (LopezMorinigo et al, 2014b;Lopez-Morinigo et al, 2016).…”
Section: Previous Suicide Attempts and Depression Were Related To Bassupporting
confidence: 80%
“…Other studies have found that the relationship of insight and suicidality may be fully mediated by depression 97 .…”
Section: Good Cognitive Insight Is Associated With Depression and Poomentioning
confidence: 93%
“…On the other hand, studies also find that insight is associated with reduced quality of life (Boyer et al, 2012;van Baars et al, 2013), lower self-esteem and increased hopelessness (Cooke et al, 2007;Hasson-Ohayon et al, 2006), as well as increased risk for depression (Mintz et al, 2004) and suicidal behavior (Barrett et al, 2010). There are however conflicting results including opposite findings concerning the relationship between insight and several of these aspects, such as suicidality (Massons et al, 2017), depressive symptoms (Cobo et al, 2016) and quality of life (Montemagni et al, 2014). These contradictory findings may be related to differences in the study populations, but may also depend on the use of different instruments to assess insight.…”
Section: Introductionmentioning
confidence: 99%